Gular Cutaneous Fibrosarcoma and Anatomophysiological Considerations for Anaesthesia in a Saddled Bichir, Polypterus endlicheri endlicheri - Ayanna Carla N. Phillips Savage; Karelma Frontera-Acevedo (Case Reports in Veterinary Medicine)
Bichirs (Polypterus spp.) have frequently been studied with regard to comparative and developmental anatomy; however, very little information has been published regarding diseases, aging changes, and medical and surgical management in these species. Neoplasia represents one such example of conditions for which a dearth of information in these species exists. There has been increasing recognition of various types of neoplasms, including cutaneous tumors, particularly in ornamental fish; some of which may be related to environmental or to infectious causes. When excision of such tumors is indicated, surgical anaesthesia is required. However, special considerations may be warranted when employing immersion anaesthesia protocols in facultative air-breathing fish that can utilise the lungs for respiration. This anatomophysiological feature of Polypterus spp. may not only influence induction and maintenance of surgical anaesthesia but may theoretically have implications for drowning. Herein, we describe the management of a case of a rapidly growing gular neoplasm in a juvenile saddled bichir and considerations for surgical anaesthesia in this “lunged” species. Induction and maintenance of surgical anaesthesia using tricaine methanesulfonate (MS-222) in this species were found to be effective at significantly lower concentrations than standard recommended doses. Histopathological analysis identified the mass as a fibrosarcoma. To the best of our knowledge, this is the first report of a cutaneous fibrosarcoma in a bichir, representing the first report of neoplasia in Polypterus spp. and the first description of surgical anaesthesia in this amphibious fish.